Air Conditioning — Optimizing Performance by Reducing Energy Consumption. Issue 5 (July 2014) - Chen, Chun-Wei; Lee, Cheng-Wen; Lin, Yu-Wei
In response to the needs of energy policy in Taiwan, it is important and urgent to promote energy efficiency in energy-intensive systems and equipment, especially air conditioning. Conventional refrigeration systems rely on experienced human beings to operate the load of components. This method is inefficient and non-reliable and causes excessive energy consumption. The present study applies the equal marginal utility theory (EMUT) from economics to a typical refrigeration system for energy saving analysis. The result of the analysis suggests that energy consumption in part-load conditions of the system was reduced by 4.74% by optimising the load on online components without significantly modifying the configuration (replacement of equipment or resetting of parameters) of the equipment. Therefore, optimising the energy use on the basis of the EMUT is highly recommended for decreasing energy consumption in air-conditioning systems.